Outcomes for Early Years’ Children in Contact with Social Services in Northern Ireland: a Data Linkage Study Protocol - Leonard, Rachel; Bunting, Lisa (International Journal of Population Data Science, 2026)
Introduction Children's social care involvement in the early years has significant implications for child development and family wellbeing. While previous research has highlighted associations between deprivation and child welfare interventions, there remains limited understanding of the timing, recurrence, and intergenerational patterns of social care contact. This study addresses these gaps using linked administrative data in Northern Ireland. Objective To examine the rates and predictors of antenatal, postnatal and early years (0-2 years) involvement with child and family social work and repeat removals of children from the same mother. Method A population-level retrospective cohort study will be conducted using linked data from the Northern Ireland Maternity System (NIMATS) and the Social Services Client Administration and Retrieval Environment (SOSCARE). Mothers with first births between 2010-2017 will form the primary cohort. Variables of interest include maternal and child demographics and deprivation. Outcomes included referral, investigation, child protection registration (CPR), and looked after child (LAC) status. Analyses will include descriptive statistics, Cox regression for time-to-event outcomes, and logistic regression for binary outcomes. Subgroup analyses will examine repeat contact and care-experienced mothers. Results Results from this study will describe the characteristics of those infants and mothers who are involved in social services in Northern Ireland, at different thresholds of involvement, and their outcomes following that involvement. Conclusions This study will add to the evidence on early identification and sustained support for at-risk mothers. Linked administrative data offers valuable insights into system dynamics and can inform targeted interventions and policy reform aimed at reducing inequalities and improving outcomes for families.